Selenium maintains Ca2+ homeostasis in sheep lymphocytes challenged by oxidative stress. - Primo Proietti; Massimo Trabalza Marinucci; Alberto Marco Del Pino; Roberto D'Amato; Luca Regni; Gabriele Acuti; Elisabetta Chiaradia; Carlo Alberto Palmerini (PLoS ONE, 2018)
Selenium (Se) is an essential element in human and animal diets, based upon a widespread range of beneficial effects that are primarily due to its antioxidant properties. While Se can be associated to anti-cancer and anti-diabetic activities, reproductive efficiency, and enhancement of the immune system, the mechanistic details of the corresponding biological processes are still largely elusive. To avoid deficiencies and increase bioavailability, Se it is generally supplied to livestock through Se-supplemented feeds or forage plants fertilized with inorganic Se. While the relationship between Ca2+ and ROS (reactive oxygen species) is well known, only a few studies have addressed the possible involvement of Se in the control of cytosolic Ca2+ in oxidative stress. The results on Ca2+ homeostasis were obtained adding exogenous Se in the form of SeO42- to sheep lymphomonocytes cultured in vitro. In particular, Se strongly attenuated 1mM H2O2-induced alteration of intracellular [Ca2+]C as well as the entry of extracellular Ca2+ into the cells with comparable EC50 values for sodium selenate accounting to 1.72 and 2.28 mM, respectively. In an ex vivo trial, it was observed that Ca2+ homeostasis can effectively be rescued in sheep lymphomonocytes exposed in vivo to a Se concentration of approximately 1.9 mM, that was achieved by feeding sheep with olive leaves previously sprayed with 500 mg/plant Na-selenate. Thus the results obtained suggest that the mode of action of selenium markedly influenced Ca2+-related signaling events. Furthermore, results clearly reveal that the protective effect of Se on Ca2+ homeostasis under oxidative challenge can be clearly and effectively achieved through an appropriate dietary regimen obtained also in a circular economy logic using pruning of olive trees treated to reduce tree drought stress.